N-Heterocyclic Carbenes (NHCs) in Asymmetric Organocatalysis - Dwivedi, Seema; Gupta, Sumanta; Das, Sajal (Current Organocatalysis, 2014)
Asymmetric synthesis is a crucial and valuable branch of synthetic chemistry. Organocatalytic methods of synthesis are known for their greener approach towards scientific developments. These involve simple molecules as catalysts that are less sensitive and can be easily and effectively employed in various systems with simple reaction conditions. In the recent past organocatalytic asymmetric syntheses have thus grasped the attentions of chemists worldwide. Remarkable contributions of N-heterocyclic carbenes have proved them to be valuable addition in this arena affording new possibilities and enabling a range of unique synthetic transformations that are otherwise inaccessible. High enantioselectivity levels have been achieved in many cases including umpolung reactions such as benzoin condensation, Stetter reaction, reactions involving enolates and homoenolates, etc. This review summarizes the recent developments in the reactions that can be carried out with NHC organocatalysts.
Keywords: cycloaddition